Characterization of Early Growth of Several Families of Manglid on Progeny Test at Sukamantri, Ciamis District - Asep Rohandi; Dede J. Sudrajat (Forest Tree Seed Technology Research & Development Center (FTSTRDC)/ Balai Penelitian dan, 2019)
One of the obstacles in the development of private forest of manglid (Magnolia champaca (Linn.) Baill ex Pierre) is the large diversity of growth in the field. Therefore, information on morphological characteristics as a quality manglid character with high productivity is needed. This study aims to characterize the early growth of several manglid families in progeny test at Sukamantri, Ciamis District. The experimental design used was a completely randomized block design consisting of 42 families from Ciamis, Tasikmalaya, Sumedang and Majalengka. Each family consists of 3 plants (3-tree plot) and 7 replications (blocks). The results showed that the growth characteristics of manglid at 1 year old had a fairly large diversity (17.96 percent−24,70 percent). The characters of the height and stem diameter have the strong positive correlation with the crown width so that the characters can be used as the criteria for selection of high productivity manglid genotypes. Families from Ciamis (101 and 104) have superiority in the character of branch-free height and total height, while families 218 (Tasikmalaya) and 406 (Majalengka) have advantages in stem diameter character. These families are quite potential as genetic sources to be developed even though they still need further evaluation.